Direct and Indirect Regeneration of Plants From Internodal and Leaf Explants of Hypericum bupleuroides Gris - Çirak, C.; Ayan, A.K.; Kevseroǧlu, K. (Botanical Society of Korea, 2007)
Species of the genus Hypericum are of considerable interest worldwide because of their medicinal properties. In-vitro culture is a useful tool for both multiplication of the genus and studying its economically important secondary metabolites. Here, we present an effective in-vitro propagation method for H. bupleuroides. Leaf and internodal explants excised from 9-week-old, in vitro-germinated seedlings were cultured on a Murashige and Skoog (MS) medium supplemented with benzyladenine (BA; 1.0 or 0.1 mg L -1 ) and 2,4-dichlorophenoxyacetic acid (2,4-D; 1.0 or 0.1 mg L -1 ). Depending on the BA and 2,4-D combination used, these cultures produced adventitious shoot buds directly on the surfaces of both types of explants as well as excessive calli. Numerous shoots were obtained when the calli from both explant types were cultured on an MS medium supplemented with 2 mg L -1 BA. Internodal explants were more responsive than leaf tissues to direct and indirect plant regeneration. After shoots that regenerated from either the calli or the explant surface were excised, rooting was best on an MS medium lacking any growth hormones. These rooted plants were then acclimatized under greenhouse conditions, and 90% of regenerants had survived. Ours is the first report of in-vitro plant regeneration from H. bupleuroides.
Keywords: Callus Induction; Hypericum Bupleuroides; Plant Growth Regulators; Plant Regeneration; Rooting; Shoot Induction